TV news and politcs: a conflicting marriage that builds reality - Becker, Beatriz (Brazilian journalism research, 2005)
This paper discusses the complex interactions between television and politics and the representation of social events on TV news programs. It is possible to conﬁ rm from the coverage of the testimony of Deputy Roberto Jeﬀ erson given to the Ethics Committee of the Brazil’s Chamber of Deputies how the Jornal da Band, the Jornal da Record and the Jornal Nacional newscasts built their reports about the reaﬃ rmation of the deputy’s denunciations and their repercussions. It is observed that each edition of the news programs is a daily version of social reality. While considering television news as an informative genre with unique characteristics and as the most striking information product of our times, this paper suggests that there is a hierarchy of values in the media discourses. Concepts and identities are built through the use of language and narrative techniques. We have identiﬁ ed the responsibility of journalists and researchers in their role of opinion makers and/or articulators of the way Brazil and the world is seen.